PIK3CA and AKT1 mutations in hidradenoma papilliferum. Issue 5 (14th October 2016) - Goto, Keisuke; Maeda, Daichi; Kudo-Asabe, Yukitsugu; Hibiya, Takashi; Hayashi, Akimasa; Fukayama, Masashi; Ohashi, Kenichi; Goto, Akiteru
Abstract : Aims: Hidradenoma papilliferum (HP) is a benign vulvar neoplasm that arises from anogenital mammary-like glands, and its morphology is similar to mammary intraductal papilloma. The aim of this study was to investigate oncogenic mutations involved in the tumourigenesis of HP. We focused specifically on PIK3CA and AKT1 mutations, which are both reported to be detected in 33% of mammary intraductal papillomas. Methods: In total, seven HP cases were analysed. Clinicopathological analyses and immunohistochemistry for oestrogen receptor, p63, smooth muscle actin (SMA), p53 and β-catenin were performed. Furthermore, PIK3CA, AKT1, BRAF and KRAS hot spot mutations were examined by Sanger sequencing. Results: Morphologically, all HPs had a papillary and tubular architecture with a biphasic pattern of epithelial and myoepithelial cells. Immunohistochemistry revealed that oestrogen receptor expression was restricted to epithelial cells, whereas p63 and SMA were exclusively expressed in myoepithelial cells. The patterns of p53 and β-catenin immunostaining suggested wild-type genotypes. Direct sequencing revealed the presence of somatic PIK3CA mutations (Ex9. c.1633G>A, p.E545K and Ex20. c.3140A>G, p.H1047R) in two of the HPs and an AKT1 (c.49G>A, p.E17K) mutation in one. BRAF and KRAS mutations were not found in any of the HP cases. Conclusions: PIK3CA and AKT1 are frequently mutated in HP tumours (29% and 14%, respectively). PIK3CA/AKT1 pathway alterations in HP further support the hypothesis that HP is the vulvar (anogenital mammary-like gland) analogue of breast intraductal papilloma.